Global issues, local contexts : the Rabi Das of West Bengal - Ganguly-Scrase, Ruchira (New Delhi : Orient Longman, 2001)
An ethnographic study of a community of shoemakers and their transformations under India's economic liberalisation.
Includes bibliographical references (p. [253]-268) and index.
Keywords: RABI DAS -- INDIA. -- WEST BENGAL -- SOCIAL CONDITIONS; SHOEMAKERS -- INDIA. -- WEST BENGAL -- SOCIAL CONDITIONS